2017
DOI: 10.1108/mrjiam-06-2017-0754
|View full text |Cite
|
Sign up to set email alerts
|

Multinational franchise entry and institutional quality: evidence from Mexican cities

Abstract: Purpose The purpose of this paper is to document the extensive heterogeneity in institutions within countries and investigate which institutional factors are the most relevant for international brands. Design/methodology/approach The paper analyzes the entry patterns of three global fast-food franchise networks in 78 Mexican cities using discrete outcome models and ordered probit in particular. To summarize the quantitative importance of the results, the analysis includes also log-linear regressions with Hec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…H4. There is a relationship between food security and community welfare, which is consistent with Laine and Vinnari (2017), , Passarini et al (2017), Kumar (2017), Danquah and Ohemeng (2017), Ram et al (2017), Arruda and Krutkowski (2017), Aluko and Knight (2017), Cheung et al (2017), and Fakos and Merino (2017).…”
Section: Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…H4. There is a relationship between food security and community welfare, which is consistent with Laine and Vinnari (2017), , Passarini et al (2017), Kumar (2017), Danquah and Ohemeng (2017), Ram et al (2017), Arruda and Krutkowski (2017), Aluko and Knight (2017), Cheung et al (2017), and Fakos and Merino (2017).…”
Section: Methodssupporting
confidence: 62%
“…Based on the publication of the Food Security and Vulnerability Atlas in 2009, 346 districts in Indonesia in 2007 could be classified into six priority groups in relation to the attempt to cope with food insecurity. This classification was based on variables causing vulnerability of absorption and food security by Sharabi (2017), Hu et al (2017), Mody et al (2017), Novak et al (2017), Singh and Singh (2017), Jalles and Andresen (2017), Wang et al (2017), Aluko and Knight (2017), Lin et al (2017), and Andrews (2017); and food security and community welfare by Laine and Vinnari (2017), , Passarini et al (2017), Kumar (2017), Danquah and Ohemeng (2017), Ram et al (2017), Arruda and Krutkowski (2017), Aluko and Knight (2017), Cheung et al (2017), and Fakos and Merino (2017). None of those previous studies had comprehensively investigated the relationship between food availability, accessibility, and absorption and food security and their effect on community welfare, especially in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…In the specific case of franchising, institutional quality also affects the decisions of potential franchisees (Fakos and Merino 2017;Lafontaine et al 2016;Wiese 2017). Fakos and Merino (2017) affirm that in Mexico, a lower institutional quality means a lower number of franchised outlets, thereby reducing the likelihood that the brand develops its presence in that country.…”
Section: Market Signals: Regulatory Quality and Gross Domestic Productmentioning
confidence: 99%
“…In the specific case of franchising, institutional quality also affects the decisions of potential franchisees (Fakos and Merino 2017;Lafontaine et al 2016;Wiese 2017). Fakos and Merino (2017) affirm that in Mexico, a lower institutional quality means a lower number of franchised outlets, thereby reducing the likelihood that the brand develops its presence in that country. In a study of countries at different stages of development, Lafontaine et al ( 2016) observed a higher perceived risk of the guarantee of investment in countries with a low institutional quality.…”
Section: Market Signals: Regulatory Quality and Gross Domestic Productmentioning
confidence: 99%
“…(1) Maternal Characteristics and Household Food Security by Wojciechowska-Solis and Soroka (2017), Coppola, et al (2017), Camilleri and Neuhofer (2017), Agolla and Lill (2017), Pesantes andDocumet (2017), Savelli, et al (2017), Koutsothanassi, et al (2017), Khare and Pandey (2017), Callado and Jack (2017), Rafay, et al (2017), andSharabi (2017), (2) Household characteristics and household food security by Sharabi, (2017), Hu, et al (2017, Mody, et al (2017), Novak, et al (2017, Singh and Singh (2017), Jalles and Andresen (2017), Wang, et al (2017), Aluko and Knight (2017), Lin, et al (2017), and Andrews, (2017), (3) Socio-economic characteristics and household food security by Laine and Vinnari (2017), Coppola, et al (2017), Passarini, et al (2017, Kumar, (2017), Danquah and Ohemeng (2017), Ram, et al (2017), Arruda and Krutkowski (2017), Aluko and Knight (2017), Cheung, et al (2017), and Fakos and Merino (2017). No previous study has comprehensively studied the relationship between maternal characteristics, household characteristics, and socio-economic characteristics and household food security, especially in Aceh, Indonesia.…”
Section: Several Previous Studies Have Found Partial Relationship Between Variables As Followmentioning
confidence: 99%